effect of bunches bagging practice in some of the natural characteristics of the fruits of the dates palm and thyme palm varieties - Mahmoud, Rend Mahmoud Abdel Ghafour; Abdel Wahab, Nabil Ibrahim (Journal of agricultural, environmental and veterinary sciences, 2018)
This Study was carried out in Khales- Diyala province in national orchard. During growth season 2016 on two cultivars (Khestawi and zahdi), the aim was to investigate the effect of bunches bagging practice with used six types of bags (control, clear polyethylene, green perforated polyethylene, perforated cloth, brown cheese cloth, white cheese cloth) to reducing the effect of high temperature degree, reducing wrinkle and dropping fruits and increase fruit water content.                 The result of study showed that: the bunches bagging treatments significantly increased the bunch weight for both cultivars. The bagging with green perforated polyethylene gave the highest bunches weight for CV. Khestawi, and bagging with perforated cloth gave the highest bunch weight for C. V. Zahdi.       Fruit weight, flesh, length and seed weight was not significant at the bunches bagging in CV. Khestawi only. While in C.V. Zahdi the bunches bagging with brown cheese cloth was significantly increased the fruit weight rate and length, bagging with white cheese cloth gave a lower seed weight rate, while the baggig treatments didn't effected of flesh weight rate.
Keywords: bagging; high temperature; date palm; khestawi; zahdi